2015
DOI: 10.1101/014779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Difference in the impacts of the neonicotinoid dinotefuran administered through sugar syrup from that through pollen paste on a honeybee colony in the long-term field experiment

Abstract: Summary We have previously examined the impact of neonicotinoid pesticides, dinotefuran and clothianidin, on honeybee Apis mellifera colonies in long-term field experiments when they were simultaneously administered through both vehicles of sugar syrup and pollen paste (Yamada et al., 2012). The independent effect of a pesticide through two vehicles has not been studied in our previous work. In this paper, we investigated the independent impact of dinotefuran through each of the two vehicles. We confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…According to our previous works (Yamada et al , 2012; Yamada et al , under submission), we have confirmed that high concentrations in sugar syrup (dinotefuran of 10 ppm; clothianidin of 4 ppm), which is used also to make pollen paste after mixing it with pollen, collapsed the honeybee colonies due to acute toxicity, low pesticide concentrations in sugar syrup (dinotefuran of 1 ppm; clothianidin of 0.4 ppm) collapsed the colonies due to chronic toxicity after having assumed the appearance of a colony collapse disorder (CCD) or an failure in wintering, and middle concentrations in sugar syrup (dinotefuran of 2 ppm; clothianidin of 0.8 ppm) damaged the colonies due to acute toxicity at the start of administration and due to chronic toxicity at the later period after having assumed the appearance of CCD and finally collapsed them.…”
Section: Introductionmentioning
confidence: 95%
“…According to our previous works (Yamada et al , 2012; Yamada et al , under submission), we have confirmed that high concentrations in sugar syrup (dinotefuran of 10 ppm; clothianidin of 4 ppm), which is used also to make pollen paste after mixing it with pollen, collapsed the honeybee colonies due to acute toxicity, low pesticide concentrations in sugar syrup (dinotefuran of 1 ppm; clothianidin of 0.4 ppm) collapsed the colonies due to chronic toxicity after having assumed the appearance of a colony collapse disorder (CCD) or an failure in wintering, and middle concentrations in sugar syrup (dinotefuran of 2 ppm; clothianidin of 0.8 ppm) damaged the colonies due to acute toxicity at the start of administration and due to chronic toxicity at the later period after having assumed the appearance of CCD and finally collapsed them.…”
Section: Introductionmentioning
confidence: 95%